2019
DOI: 10.5812/erms.88228
|View full text |Cite
|
Sign up to set email alerts
|

Challenges of Clinical Education in Midwifery and Strategies to Improve It: A Qualitative Study

Abstract: Background: Recognizing the barriers to clinical training and providing appropriate solutions to them significantly enhance the quality of clinical training.Objectives: The present study was conducted to evaluate the challenges of midwifery clinical training, and propose solutions from the perspective of midwifery instructors and students. Methods:The present qualitative study was conducted on 10 midwifery instructors and 10 midwifery students using semistructured interviews (n = 12) and focus groups (n = 8). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 23 publications
2
6
0
Order By: Relevance
“…This result indicated that midwifery students complained, some staffs' were ordered them to be outside of the room while they were performing complicated procedures like repairing perineal-tear and resuscitating neonates. This is in line with a study conducted in Belgium and Iran; in the case of pathologies like post-partum bleeding, preceptors and staffs didn't explain what is going to be done and why rather they pushed aside for the students that lead midwifery students not to participate in such acute and real situations and make them demotivated to learn (19,23).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…This result indicated that midwifery students complained, some staffs' were ordered them to be outside of the room while they were performing complicated procedures like repairing perineal-tear and resuscitating neonates. This is in line with a study conducted in Belgium and Iran; in the case of pathologies like post-partum bleeding, preceptors and staffs didn't explain what is going to be done and why rather they pushed aside for the students that lead midwifery students not to participate in such acute and real situations and make them demotivated to learn (19,23).…”
Section: Discussionsupporting
confidence: 75%
“…This result is supported by a study conducted in Ethiopia and Iran; absences of a variety of cases in clinical sites other than the teaching institutions make students perform the routine procedures rather than gaining new and complicated skills. In some clinical sites especially in health centers, midwifery students may nish the time allocated to clinical practice without attending the minimum number of normal delivery (18,19).…”
Section: Discussionmentioning
confidence: 99%
“…This result indicated that midwifery students complained, some staffs’ were ordered them to be outside of the room while they were performing complicated procedures like repairing perineal- tear and resuscitating neonates. This is in line with a study conducted in Belgium and Iran; in the case of pathologies like post-partum bleeding, preceptors and staffs didn’t explain what is going to be done and why rather they pushed aside for the students that lead midwifery students not to participate in such acute and real situations and make them demotivated to learn [ 19 , 23 ].…”
Section: Discussionsupporting
confidence: 72%
“…This result is supported by a study conducted in Ethiopia and Iran; absences of a variety of cases in clinical sites other than the teaching institutions make students perform the routine procedures rather than gaining new and complicated skills. In some clinical sites especially in health centers, midwifery students may finish the time allocated to clinical practice without attending the minimum number of normal delivery [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on evidence, the professional capabilities of students have decreased compared to the previous decades [ 8 , 9 ]. The results of a qualitative study showed that an inappropriate educational atmosphere and an inefficient curriculum are the main issues of midwifery education in Iran [ 10 ]. Moreover, studies report students lack skills and efficiency in clinical settings despite their adequate theoretical knowledge [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%